PENGARUH FAKTOR MAKRO EKONOMI DAN PERTUMBUHAN PERUSAHAAN TERHADAP LEVERAGE DAN NILAI PERUSAHAAN - Sujoko Sujoko (University of Merdeka Malang, 2016)
The purpose of this empirical study is to investigate the influence of macro economic,growth firm on leverage and value of the firm.This study uses Agency Free Cash Flow, Static trade off Theory, Pecking Order Theory and Signaling Theory.This study uses empirical data from Indonesian Capital Market Directory 2015 issued By Indonesian Stock Exchange. This research uses quantitative analysis. The Population of the research are manufacturing firm listed in Indonesian Stock Exchange. The hypothesis test uses structural equation model-ing with the degree of signifance at 0.05. Sample in this study are manufacturing company listed in Indone-sian Stock Exchange during 2012-2014. As much as 75 manufacturing firm listed in Indonesian Stock exchange were taken as a sample using a purposive sampling method. The data were there analyzed by Structural Equation Modeling (SEM). The Result of the study show that: (1) Macro economic factor have negative significant influence on leverage with p value 0.06 (2) Growth firm have significant influences on leverage with value 0.004 (3) Macro economic have negative t influences on value of the firm with p value 0.006 (4) Growth firm have positive significant influence on value of the firm with p value 0.005 (5) Leverage have negatives significant influence on value of the firm with p value 0.006 The result of the study is support to Agency Free Cash Flow,Jensen (1986),Static Trade off Theory, Pecking Order Theory, Myers and Majluf (1984) and Signaling Theory, Ross (1977